ANTI-DIABETIC EFFECTS OF ZHUODUQING FORMULA, A CHINESE HERBAL DECOCTION, ON A RAT MODEL OF TYPE 2 DIABETES - Feng, Xiao-Tao; Tang, Shu-Yan; Jiang, Yun-Xia; Zhao, Wei (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Zhuoduqing formula (ZDQ) is a Chinese herbal decoction and used to treat type 2 diabetes in clinicalpractice, but the potential evidence needs to be provided.Materials and Methods: Type 2 diabetic model rats were induced by feeding high fat diet (HFD) and intraperitonealinjection of streptozotocin (STZ). The model rats were given ZDQ for 4 weeks. Insulin sensitivity was evaluated byhomeostasis model assessment of basal insulin resistance (HOMA-IR) and intraperitoneal glucose tolerance test(IPGTT). Blood insulin and tumour necrosis factor-α (TNF-α) levels as well as SOCS-3 levels in skeletal muscles wereanalyzed by ELISA.Results: ZDQ significantly decreased fasting blood glucose, ameliorated HOMA-IR and IPGTT, and reducedtriglyceride and total cholesterol in type 2 diabetic rats. Moreover, ZDQ remarkably lowered blood TNF-α levels andinhibited SOCS-3 levels in skeletal muscles.Conclusion: The results display that ZDQ performs anti-diabetic functions in type 2 diabetic rats induced by feedingHFD and intraperitoneal injection of STZ.